Investigation of Nanoscopic Dynamics and Potentials by Interferometric Scattering Microscopy - Ortega Arroyo, Jaime (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis offers a unique guide to the development and application of ultrasensitive optical microscopy based on light scattering. Divided into eight chapters, it covers an impressive range of scientific fields, from basic optical physics to molecular biology and synthetic organic chemistry. Especially the detailed information provided on how to design, build and implement an interferometric scattering microscope, as well as the descriptions of all instrumentation, hardware interfacing and image processing necessary to achieve the highest levels of performance, will be of interest to researchers now entering the field.